The Imperatives of Quality Services in Condition of European Integration - Natalia Remesovski (CES Working Papers, 2012)
Quality includes the technical side or strictly linked to intrinsic characteristics and properties of the product or service and it can be defined as a set of properties and characteristics of a product or service, which gives it its ability to meet the needs expressed or implied. The liberalization of international trade by value, internationalization and globalization and the development spheres of service, the bar in quality always rises and quality is a key factor in customers decision to choose a particular company or another.
Keywords: M31; M38; 330; Quality; dimensions of service quality; service quality; European quality policy; imperatives of the service quality Romania